Science and technology transfer – rural women’s impact in Sri Lanka - Hirimburegama, Kshanika; Hirimburegama, W.K.; Ratnayake, S. (My University, 2012)
i gi olochnology & Community Service Center, University of Colombo located in a rural |iC/or at Weligatta, Hambantota (250 km from capital Colombo) is an on-going project tii u:o 2000, on rural de velopment through science & technology. This is the first ever kind i in voloped by a University system in Sri Lanka in collaboration with government & other | •< ganizations. The attempt is also made to educate and empower the rural women and llmroby to improve rural economy. Through the Science & Technology (S&T) activities, (/to potential for improvement of rural sector income was clearly seen. Both men and women showed enthusiasm to take up novel technology but in different aspects: women "inro in in-house science & technology such as processed food technology and mushroom cultivations while men in outdoor cultivations. It also revealed that when women are empowered, the family in general is looked after as the burden on the women who contribute significantly to the health and wealth of the family. The training i a i igrammes conducted clearly showed the enthusiasm among the young, to adopt novel im-.hnologyin agriculture. It also showed the capabilities of the youngergeneration in the 11 a nl sector and their commitment. Also there was a clear economic improvement of the people: a ten-fold increase through the use ofS& Tin the cultivations. Increased income I fer all the stakeholders is the main driving force in the success of adopting new tov.hnology. Indirectly crimes would be reduced as work is available and villages have a | ttope forthemselves and their children: a tendency already seen in the area